Free-cutting copper-nickel-tin-tellurium alloy and preparation method thereof
By adding Ni, Sn and Te elements to the copper-nickel-tin alloy, Cu2Te compounds are formed, and a specific process flow is adopted to solve the problem of insufficient cutting performance of copper-nickel-tin alloy, achieving high strength, hardness and wear resistance. It significantly improves cutting performance and is suitable for environmentally friendly materials needs in the new energy vehicle industry.
Patent Information
- Application Number
- CN202411198616.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-31
AI Technical Summary
The existing copper-nickel-tin alloys have shortcomings in cutting performance and are difficult to replace the toxic beryllium bronze materials. At the same time, they need to have high strength, high hardness and good wear resistance to meet the needs of the new energy vehicle industry.
By adding Ni, Sn and Te elements to the copper matrix, Cu2Te compound is formed, and combined with homogenized annealing, extrusion, welding and tensile processes, the composition and microstructure of the alloy are controlled to improve its strength, hardness and cutting performance.
It achieves high strength, hardness and wear resistance, and significantly improves the cutting performance of the alloy. The tensile strength reaches more than 500MPa, the hardness is more than 170HV, and the cutting performance reaches more than 80% of C17300. It is beryllium-free and lead-free, and it is environmentally friendly and feasible. .
Smart Images

Figure CN119220853A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of copper alloys, and in particular relates to a free-cutting copper-nickel-tin-tellurium alloy and a preparation method thereof. Background Art
[0002] Test probes are a common type of precision electronic components in the electronics industry, including semiconductor test probes, wiring harness test needles, PCB test needles, etc. Driven by the localization process, along with capital operations and technology upgrades, both low-end wiring harness test needles, PCB test needles and high-end semiconductor test probes have shown a strong growth momentum. In addition, the new energy vehicle industry has experienced explosive growth, and there is also a strong demand for chemical composition and capacity probes used in supporting new energy power batteries.
[0003] In this type of products, small-sized probes require materials that not only have high strength, high hardness, high wear resistance and good cutting performance, but also have certain electrical conductivity. Currently, the material that can meet this condition is mainly lead-added beryllium bronze, but beryllium and its oxides are toxic substances, which are extremely harmful to the human body and the environment during the production process and waste recycling. Lead itself is toxic. During the production process, lead will exist in the metal vapor generated by melting and casting processes, posing a threat to human health and environmental hygiene. Therefore, beryllium-free and lead-free substitution in the probe industry has gradually become a new demand direction.
[0004] In order to reduce the impact of beryllium bronze on human body and environment, copper processing enterprises and scientific research institutions in various countries around the world have begun to conduct feasibility studies on beryllium bronze alternatives, and copper-nickel-tin alloy is a feasible alternative. Copper-nickel-tin alloys such as C72900, C72700, and C72650 alloys have comprehensive properties such as high strength, high hardness, and high wear resistance, and are ideal materials to replace beryllium bronze, but their cutting performance is poor. Based on this, it is urgent to develop an environmentally friendly copper-nickel-tin alloy material with high strength, high hardness, high wear resistance, and good cutting performance. Summary of the invention
[0005] The first technical problem to be solved by the present invention is to provide a free-cutting copper-nickel-tin-tellurium alloy having high strength, high hardness, high wear resistance and good cutting performance.
[0006] The technical solution adopted by the present invention to solve the first technical problem is: a free-cutting copper-nickel-tin-tellurium alloy, the weight percentage composition of the alloy is Ni: 5.5-15.5wt%, Sn: 4.5-8.5wt%, Te: 0.1-0.6wt%, and the balance is Cu and inevitable impurities.
[0007] The Ni element has the same crystal structure and similar lattice constant as the matrix Cu element. The Ni element added to the copper matrix can be infinitely dissolved in the copper matrix, producing a strong solid solution strengthening effect, and improving the strength, hardness and corrosion resistance of the alloy. The Ni element in the alloy can also combine with the Sn element and a small amount of Cu element to form a compound phase that precipitates from the matrix, purifies the matrix and plays a role in precipitation strengthening. When the Sn element content in the Cu-Ni-Sn alloy is fixed, increasing the Ni element content can improve the strength, plasticity and elastic modulus of the alloy, and the processing performance of the alloy is also improved. When the Ni and Sn contents are increased at the same time, the mechanical properties of the alloy are improved to varying degrees, but the electrical conductivity of the alloy is significantly reduced, and when the Ni and Sn contents exceed a certain value, the electrical conductivity and mechanical properties of the alloy are reduced at the same time. When the Ni content is too low, the Ni content dissolved in the copper matrix is reduced, and the effect of improving the strength and hardness of the alloy is not obvious. At the same time, the strengthening phase cannot be effectively precipitated, resulting in low electrical conductivity of the alloy. Therefore, the Ni content of the alloy of the present invention is controlled at 5.5-15.5wt%.
[0008] The Sn content has a decisive influence on the alloy strengthening mode of Cu-Ni-Sn alloy during the aging process. When the Sn content is lower than 4wt%, all Sn elements are dissolved in the copper matrix and spinodal decomposition cannot occur. The strengthening mechanism of the alloy is solid solution strengthening, and the alloy strength cannot be effectively improved. When the Sn content is higher than 4wt%, the strengthening mechanism of the alloy is spinodal decomposition. In addition to the solid solution strengthening of some Sn elements dissolved in the copper matrix, the remaining Sn elements will be decomposed by spinodal decomposition to form (Cu x ,Ni 1-x )3Sn precipitates from the matrix in the form of Sn, producing spinodal decomposition strengthening, forming a dense and uniform spinodal structure during the aging process, and the strength of the alloy is effectively improved. Therefore, the Sn content is generally higher than 4wt%. However, since Sn is prone to segregation during the casting process, if the Sn content is higher than 8.5wt%, it will have an adverse effect on the alloy performance and increase the difficulty and cost of alloy preparation. Therefore, the Sn content of the alloy of the present invention is controlled at 4.5-8.5wt%.
[0009] Te element can form compound Cu2Te with copper in the cast state. This compound forms eutectic with copper at a higher temperature (about 1084℃), and is distributed in the copper matrix in the form of dispersed and soft second phase particles, which refines the grains and significantly improves the cutting performance of the alloy. At the same time, due to the low solubility of Te element in copper, the influence on the electrical and thermal conductivity of the alloy is low. Due to the combined effect of dispersion strengthening and fine grain strengthening caused by the addition of Te element, the alloy has excellent properties such as strength, hardness, wear resistance, and ductility, and has good cutting performance. In addition, the addition of Te element will not produce harmful substances, which can avoid harm to the environment and human body.
[0010] Preferably, in the longitudinal section of the free-cutting copper-nickel-tin-tellurium alloy of the present invention, the average grain size is 5 to 50 μm, and the average particle size of the Te-containing compound is 0.1 to 10 μm.
[0011] Preferably, in the microstructure of the longitudinal section of the free-cutting copper-nickel-tin-tellurium alloy of the present invention, the average grain size is 5 to 50 μm, and the average particle size of the Te-containing compound is 0.1 to 10 μm, measured by the long axis. In the alloy, the size of the grains and compound particles is closely related to the alloy properties. The finer the grains and the average particle size of the Te-containing compound, the more obvious the fine grain strengthening and dispersion strengthening effects of the alloy, and the more conducive to the improvement of the strength and hardness of the alloy. At the same time, the fine dispersion distribution of the Te compound is conducive to the improvement of the cutting performance.
[0012] Preferably, in the microstructure of the longitudinal section of the free-cutting copper-nickel-tin-tellurium alloy of the present invention, the amount of Te compounds per unit area is 5×10 9 pcs / m 2 The number of particles of Te-containing compounds with a size of 5 μm or less in all Te-containing compounds accounts for more than 90%, so as to ensure that the alloy has good cutting performance while obtaining good strength, hardness and wear resistance, and at the same time avoid cracking caused by increased brittleness of the alloy.
[0013] Preferably, the free-cutting copper-nickel-tin-tellurium alloy of the present invention also contains at least one element selected from Zn, Mn, Nb, Zr, Pb, Fe, Mg, Si and Ti in a total amount not exceeding 1.0wt%. The addition of the above trace elements can be dissolved in the copper matrix, play a solid solution strengthening effect, improve the strength, hardness and wear resistance of the alloy, etc. At the same time, the addition of the above trace elements helps to refine the grains, promote the precipitation of alloy elements, and enhance the aging strengthening effect, so that the copper alloy has good strength, hardness and cutting performance. However, when the total amount of the above trace elements added exceeds 1.0wt%, the solubility limit will be reduced, and coarse precipitation phase particles tend to be precipitated, which is not conducive to the improvement of the strength, hardness and cutting performance of the alloy. Therefore, the total amount of the above trace elements is controlled below 1.0wt%.
[0014] The free-cutting copper-nickel-tin-tellurium alloy of the present invention has a tensile strength of more than 500 MPa, a hardness of more than 170 HV, and a cutting performance of more than 80% of that of C17300.
[0015] The free-cutting copper-nickel-tin-tellurium alloy of the present invention has a tensile strength of more than 900 MPa and a hardness of more than 300 HV after aging.
[0016] The second technical problem to be solved by the present invention is to provide a method for preparing a free-cutting copper-nickel-tin-tellurium alloy.
[0017] The technical solution adopted by the present invention to solve the second technical problem is: a method for preparing a free-cutting copper-nickel-tin-tellurium alloy, wherein the process flow for preparing the alloy includes: melting → homogenization annealing → extrusion → butt welding → coil wire drawing → solution treatment → finished product drawing → straightening, wherein the homogenization annealing temperature is 750-900°C, and the holding time is 5-10h; the extrusion temperature is 750-900°C, the extrusion ratio is 25-100, and the surface temperature of the extruded billet during extrusion is 650-850°C; the cold deformation of the coil wire drawing is 40-80%.
[0018] 1) Melting and casting: The alloy of the present invention adopts a semi-continuous casting method to produce ingots. The amount of ingredients is calculated according to the alloy composition, and then the raw materials are melted in a medium frequency induction furnace. A medium frequency induction melting furnace is used for smelting, and the raw materials are electrolytic copper, electrolytic nickel, industrial pure tin and pure tellurium. After the alloy melt is kept warm and mixed evenly, it is cast. The smelting and casting temperature is 1150-1350°C, the casting speed is 2-5m / h, and the electromagnetic stirring crystallizer is used for casting. The electromagnetic stirring refines the casting structure to avoid macroscopic segregation of the alloy Sn component, and at the same time, the Te compound is evenly distributed in the ingot structure in a block shape, effectively reducing the cracking of the alloy structure. The electromagnetic stirring process can break up the larger dendrites produced in the early stage of melt solidification in the crystallizer, increase the nucleation rate, and control the grain size of the continuous casting billet, thereby reducing the diffusion channel of the tin element, reducing Sn segregation, and effectively improving the performance of the ingot.
[0019] 2) Homogenization annealing: The copper-nickel-tin-tellurium alloy of the present invention is subjected to homogenization annealing treatment at 750-900°C for 5-10 hours before extrusion. The temperature of homogenization annealing is 750-900°C and the holding time is 5-10 hours. Under this condition, the alloy elements can diffuse, promote the uniform distribution of the alloy components, and improve microsegregation. Homogenization annealing can form a homogeneous structure in the alloy to reduce chemical or metallurgical segregation that may occur due to solidification. Homogenization annealing can also improve the plasticity and mechanical properties of the alloy, improve the uniformity of the alloy hardness, and at the same time improve the elongation and fatigue resistance of the alloy.
[0020] 3) Extrusion: The alloy ingot after homogenization annealing is induction heated to 750-900℃, and the extrusion ratio is 25-100. The surface temperature of the extruded billet is 650-850℃. When the alloy ingot is heated to 750-900℃, the alloy structure can be guaranteed to have sufficient fluidity, thereby ensuring the uniform distribution of Cu2Te compounds. If the extrusion temperature of the alloy ingot is lower than 750℃, it is easy to be extruded and immovable, and extrusion at a lower temperature is easy to increase the deformation structure of the alloy, which is not conducive to the subsequent production; if the extrusion temperature of the alloy ingot is higher than 900℃, it will cause the dynamic recrystallization structure of the alloy to grow, affecting the subsequent processing and heat treatment of the alloy. The extrusion ratio of 25-100 is conducive to the formation of new equiaxed crystals in the alloy structure and reducing the anisotropy of the alloy. When the extrusion ratio is lower than 25, due to the low degree of extrusion deformation, the extruded billet structure is prone to ingot cast structure, and the alloy performance deteriorates; if the extrusion ratio exceeds 100, it is easy to cause the ingot to be extruded. The surface temperature of the extruded billet is controlled at 650-850°C during extrusion, followed by rapid water cooling, so that a fine and uniform alloy structure can be obtained, so that the Te compound is dispersed in strips and particles, improving the hot working properties of the alloy and meeting the plasticity required for subsequent cold working. Preferably, the surface temperature of the extruded billet during extrusion is 700-850°C.
[0021] 4) Welding and stretching: The finished bars are produced by welding and coil wire stretching. After cold deformation, the soft Te compound is dispersed in the grains or on the grain boundaries in the form of strips. In order to obtain a better aging strengthening effect for the finished bars, the cold deformation of the stretching is controlled at 40-80%. The cold deformation of 40-80% can form an appropriate amount of dislocation and deformation structure inside the alloy, provide channels and primary phases for the later precipitation, and is conducive to the formation of an ideal microstructure in the later solid solution treatment and aging heat treatment process. As the degree of cold deformation of the stretching increases, the tensile strength of the alloy increases, while the elongation at break decreases. However, if the cold deformation is too large, exceeding 80%, the deformation resistance of the alloy will increase greatly, affecting the alloy processing and even breaking; if the deformation is too low, less than 40%, it will cause uneven deformation of the alloy and damage the alloy. If the finished bar specifications are large, the straight bar stretching process is adopted.
[0022] 5) Solution treatment: In order to meet the requirements of the subsequent cold deformation processing, the stretched aisle billet needs to be solution treated at 700-850℃, kept warm for 0.5-3h, and the cooling rate after holding warm is above 50℃ / s. Compared with the stretched state, the Te compound in the solid solution state is dispersed in strips or particles, and its contour is passivated. Solution treatment is one of the most important process of the alloy of the present invention, and the quality of solid solution directly affects the microstructure and final performance of the alloy. In order to obtain a uniform and fine alloy structure, the temperature of the solution treatment of the alloy of the present invention is 700-850℃, the holding time is 0.5-3h, and a rapid cooling treatment of more than 50℃ / s is performed after holding warm. If the temperature of the solution treatment is too low and the holding time is too short, the elements are not completely dissolved, which will affect the subsequent precipitation phase, resulting in low strength and hardness of the alloy; if the temperature of the solution treatment is too high and the holding time is too long, the alloy grains will continue to grow or even overburn after the elements are dissolved, which will also lead to poor alloy performance. When the alloy of the present invention is solution treated, after being kept at 700-850°C for 0.5-3h, the copper matrix undergoes recrystallization, the cold deformation structure is basically eliminated, the grains do not grow significantly, and the amount of the precipitated second phase is significantly reduced, dissolved in the copper matrix, providing sufficient power for subsequent aging treatment. After the heat preservation, a rapid cooling treatment of more than 50°C / s is carried out, which is conducive to reducing the agglomeration of the Te-containing compound phase during the cooling process, inhibiting the deformation and cracking of the alloy, ensuring the precipitation of fine dispersed compounds in the subsequent deformation heat treatment process, and further improving the strength and hardness of the alloy.
[0023] 6) Finished product stretching: After solution treatment, the finished product stretching with a deformation of 10-40% can make the alloy obtain a smooth surface, specific microstructure and performance. After the alloy solution treatment, a certain finished product stretching can promote the formation and redistribution of fine grains and precipitated phases, further improve the strength and hardness of the alloy, play a deformation strengthening effect, and at the same time help improve the elongation of the alloy. In addition, the cold deformation effect of different degrees of finished product stretching is also different. As the cold deformation amplitude increases, the peak value of the hardening curve of the alloy will also increase.
[0024] 7) Straightening: Straighten the above products in a straightening machine to obtain finished products.
[0025] Preferably, an aging treatment is performed before stretching and after solution treatment, the aging treatment temperature is 320-400°C, the holding time is 1-6h, and air cooling or water cooling treatment is performed after the holding is completed. The above aging treatment is conducive to the precipitation and uniform dispersion distribution of the precipitate phase, so that the alloy obtains higher strength and wear resistance. At the same time, due to the fine dispersion distribution of the Cu2Te compound, the cutting performance of the alloy is significantly improved. When the aging temperature is higher than 400°C and the holding time exceeds 6h, the precipitate aggregation and excessive growth of the grains and precipitate phases are prone to occur, which is not conducive to the strengthening effect of the alloy; when the temperature is lower than 320°C and the holding time is lower than 1h, it is difficult to achieve the precipitation strengthening effect, and at the same time, the copper matrix is not fully recrystallized, and more processing tissues remain in the organization, and excellent product performance cannot be achieved.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] (1) The free-cutting copper-nickel-tin-tellurium alloy of the present invention forms a precipitated phase containing Cu2Te compounds by adding elements such as Ni, Sn, and Te to the copper matrix, thereby improving the strength, hardness, and wear resistance of the alloy. At the same time, the addition of Te element can significantly improve the cutting performance of the alloy, thereby significantly improving the cutting performance of the alloy. Based on this, the tensile strength of the alloy of the present invention is above 500 MPa, the hardness is above 170 HV, and the cutting performance is above 80% of that of C17300.
[0028] (2) The free-cutting copper-nickel-tin-tellurium alloy of the present invention is beryllium-free and lead-free, has excellent performance and is environmentally friendly, and can meet the application requirements of the test probe industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a microstructure cross-sectional view along the longitudinal section direction of the finished rod sample of Example 1. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below with reference to the accompanying drawings.
[0031] The ingredients are prepared according to the compositions of the copper-nickel-tin-tellurium alloys and the comparative examples in Examples 1 to 14 in Table 1. During smelting, the temperature of the smelting furnace is controlled at 1150 to 1350° C., the casting speed is 2 to 5 m / h, and the composition test is performed after smelting. Compensation or dilution is performed according to the composition results. After the composition is qualified, slag is removed, degassing and heating are performed; when the temperature of the molten copper is constant at 1250 to 1280° C., semi-continuous casting is performed; and then a homogenization annealing treatment is performed at 750 to 900° C. for 5 to 10 hours; Then the extrusion process is carried out, the ingot extrusion temperature is 800-900℃, and the holding time is 1h; after the head and tail defective sections are cut off from the extruded bar, the coil is welded, and then multiple coil wire stretching is carried out, and the cold deformation is controlled at 40-80%; then the solution treatment is carried out at 700-850℃ for 0.5-3h to obtain a uniform and fine alloy structure; then the finished product is stretched with a deformation of 10-40%, and finally straightened on a straightening machine to obtain a finished bar. The obtained samples are evaluated for characteristics under the following conditions.
[0032] The room temperature tensile test is carried out in accordance with "GB / T 228.1-2021 Metallic Materials Tensile Test Part 1: Room Temperature Test Method" on an electronic universal mechanical properties testing machine to test tensile strength, elongation, yield strength and other properties.
[0033] Vickers hardness is tested in accordance with GB / T 4340.1-2009 “Vickers hardness test for metallic materials”.
[0034] The grain size of the alloy was observed using an optical microscope, and the average grain size was calculated based on the results.
[0035] Take the longitudinal section, observe the size and quantity of Te compounds in the alloy under transmission electron microscope and scanning electron microscope, and make statistical data. The specific operation is as follows: along the longitudinal section of the alloy, take 25μm×40μm (1000μm 2 ) as the basic unit to observe its organization; 10 rectangles at different positions in the field of view were selected to count the size of Te-containing compounds and the number of their particles, and finally the average value was taken as the basis for judgment.
[0036] Figure 1 It is a microstructure cross-sectional view along the longitudinal section direction of the finished rod sample of Example 1. Figure 1 The black stripe and black dot structures inside the two white elliptical dashed boxes are Te compounds distributed in stripe and granular forms.
[0037] Since the cutting performance is inversely proportional to the turning force, the cutting performance is characterized by the magnitude of the turning force. Taking the main turning force of C17300 as the reference value, the finished bar samples of the same size and specifications were tested with the C17300 bar. The turning speed was 3000rpm, the feed speed was 0.1mm / r, and the cutting depth was 0.8mm. The main turning force of the C17300 bar is A, and the main turning force of the finished bar sample is B. Then B / A is the ratio of the main turning forces of the two, and (A / B)×100% is the cutting performance of the corresponding finished bar sample.
[0038] By comparing the overall performance of the alloy of the embodiment of the present invention with the alloy of the comparative example, it is found that the tensile strength of the alloy of the present invention can reach more than 500 MPa, the hardness is more than 170 HV, and the cutting performance can reach more than 80% of C17300. It can be found from the comparative example that when the alloy composition does not meet the requirements, the microstructure, strength, hardness, cutting performance, etc. of the alloy do not meet the requirements.
[0039] Table 1 Composition of Examples and Comparative Examples
[0040]
[0041] Table 2 Microstructure and performance of embodiments and comparative examples
[0042]
Claims
1. A free-cutting copper-nickel-tin-tellurium alloy, characterized in that: The alloy comprises Ni: 5.5-15.5wt%, Sn: 4.5-8.5wt%, Te: 0.1-0.6wt%, and the remainder is Cu and inevitable impurities.
2. The free-cutting copper-nickel-tin-tellurium alloy according to claim 1, characterized in that: In the microstructure of the longitudinal section of the alloy, the average grain size is 5 to 50 μm, and the average particle size of the Te compound is 0.1 to 10 μm, measured by the long axis.
3. The free-cutting copper-nickel-tin-tellurium alloy according to claim 1, characterized in that: In the microstructure of the longitudinal section of the alloy, the number of Te compounds per unit area is 5×10 9 pcs / m 2 The number of particles of the Te-containing compound having a size of 5 μm or less accounts for more than 90% of all the Te-containing compounds.
4. The free-cutting copper-nickel-tin-tellurium alloy according to claim 1, characterized in that: The alloy also contains at least one element selected from Zn, Mn, Nb, Zr, Pb, Fe, Mg, Si and Ti in a total amount not exceeding 1.0wt%.
5. The free-cutting copper-nickel-tin-tellurium alloy according to claim 1, characterized in that: The alloy has a tensile strength of 500 MPa or more, a hardness of 170 HV or more, and a cutting performance of more than 80% of that of C17300.
6. The free-cutting copper-nickel-tin-tellurium alloy according to claim 1, characterized in that: The tensile strength of the alloy after aging is above 900 MPa and the hardness is above 300 HV.
7. The method for preparing the free-cutting copper-nickel-tin-tellurium alloy according to any one of claims 1 to 4, characterized in that: The process flow for preparing the alloy includes: melting and casting → homogenizing annealing → extrusion → butt welding → coil wire drawing → solution treatment → finished product drawing → straightening, wherein the homogenizing annealing temperature is 750-900°C, and the holding time is 5-10h; the extrusion temperature is 750-900°C, the extrusion ratio is 25-100, and the surface temperature of the extruded billet during extrusion is 650-850°C; the cold deformation of the coil wire drawing is 40-80%.
8. The method for preparing a free-cutting copper-nickel-tin-tellurium alloy according to claim 7, characterized in that: The temperature of the solution treatment is 700-850°C, the holding time is 0.5-3h, and the cooling rate after holding is above 50°C / s.
9. The method for preparing a free-cutting copper-nickel-tin-tellurium alloy according to claim 7, characterized in that: Aging treatment is carried out before stretching and after solution treatment. The aging treatment temperature is 320-400°C and the insulation time is 1-6h. After the insulation is completed, air cooling or water cooling is carried out.
Citation Information
Cited By
Copper-nickel alloy and preparation method and application thereof
CN121718749A
Novel copper-tungsten alloy material and preparation process
CN121931413A
